2019
DOI: 10.1007/s00382-019-04636-0
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic gridded product for daily precipitation extremes over the United States

Abstract: Gridded data products, for example interpolated daily measurements of precipitation from weather stations, are commonly used as a convenient substitute for direct observations because these products provide a spatially and temporally continuous and complete source of data. However, when the goal is to characterize climatological features of extreme precipitation over a spatial domain (e.g., a map of return values) at the native spatial scales of these phenomena, then gridded products may lead to incorrect conc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 53 publications
0
55
0
Order By: Relevance
“…We apply the spatial data analysis outlined in Risser et al (2019) to characterize the spatially-complete climatological distribution of extreme precipitation based on measurements from weather stations, as well as to quantify the relationship between the ENSO indices and daily extremes. An important feature of the Risser et al (2019) analysis is that it allows one to estimate the distribution of extreme precipitation even for locations where no data are available. Furthermore, their methodology can be used for a large network of weather stations over a heterogeneous spatial domain like the western US, which is critical for the problem at hand.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We apply the spatial data analysis outlined in Risser et al (2019) to characterize the spatially-complete climatological distribution of extreme precipitation based on measurements from weather stations, as well as to quantify the relationship between the ENSO indices and daily extremes. An important feature of the Risser et al (2019) analysis is that it allows one to estimate the distribution of extreme precipitation even for locations where no data are available. Furthermore, their methodology can be used for a large network of weather stations over a heterogeneous spatial domain like the western US, which is critical for the problem at hand.…”
Section: Methodsmentioning
confidence: 99%
“…Using station-specific estimates of the climatological coefficients, we next apply spatial statistical methods (via second-order nonstationary Gaussian processes) to infer the underlying climatology over a fine grid via kriging (again see Risser et al 2019 for full details). This approach yields fields of best estimates of the climatological coefficients, denoted ̂0 � ,̂1 � ,̂ � ,̂ � ∶ � ∈ G , where G is the 0.25° grid of M = 13,073 grid cells over CONUS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavanaugh and Gershunov (2015) assessed the impact of spatio-temporal averaging on the tail structure of precipitation distributions and showed that spatial averaging can result in greater reduction in volatility than does temporal averaging, in regions where relatively long-lived extreme precipitation-producing systems such as atmospheric rivers are important. Due to the fractal nature of daily or sub-daily precipitation, the wisdom of gridding such a heterogeneous function has been called into question by Risser et al (2018) who offer an alternative approach using spatial statistics to grid precipitation extremes from station data directly.…”
Section: Precipitation Datamentioning
confidence: 99%
“…the precipitation product used to drive the models (Te Linde et al, 2007), which was here different for mHM than for the other models. These products may underestimate extreme rainfall or the spatial dependence of extreme precipitation at different locations because spatial smoothing or averaging during the gridding process reduces variability (Risser et al, 2019). The importance of input uncertainty is particularly pronounced if we are interested in future changes (Chen et al, 2014).…”
Section: Flood Triggersmentioning
confidence: 99%